The "Death Loop" challenge: A few remarks - Kulviecas, L. (Psichologija, 1962)
The article deals with famous mechanical problem on the weighty point of the movement of the vertical circle, making it clear that in the case of one-way communication (even when the considered point is the object of an additional tangential force, causing its uniform circular motion) a material point can never break away from the links at the highest point of the curve. By analogy it also cannot separate from the links at the highest point of the vertical trajectory: 1) a homogeneous sphere, rough rolling circular cylinder with its axis horizontal, spherical center of mass always in the same in a vertical plane inside and 2) a system of three identical homogeneous balls up so that while remaining in a vertical plane their centers coincide with peaks ·equilateral triangle, with a side equal the diameter of the spheres ·(two supporting spheres roll on the inside of that rough cylinder, while the whole system is composed like a cart, moving; "death loop"). The results showed the formulation and solution of the elementary mechanics "death loop" tasks of the: · there are some inaccuracies; moreover, a critical remark about the work specifically deals with this type of task.